(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2023)
Despite advancements in reconstructive surgery and a growing understanding of anorectal malformation (ARM) anatomy, boys still commonly experience urinary tract injuries after ARM reconstruction. These injuries include postoperative rectourethral fistula (RUF), urethral stricture or stenosis, bladder dysfunction or injury, prostatic injury, ureteral injury, and vas & seminal vesicle injury. Some of these injuries are immediately apparent during surgery, while others present later in follow-up. This article details the causes, symptoms, management, and prevention protocols for urogenital tract injuries during ARM reconstruction in boys. Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1&2): 44-49